إدارة فيــروس كورونا بإندونيسيا في ضوء مقاصد الشريعـــــــــة - Alif Rifdan Syah (Jurnal Ilmiah AL-Jauhari: Jurnal Studi Islam dan Interdisipliner, 2021)
This research is under the topic of "Managing Coronavirus in Indonesia in the perspective of Maqasid Sharia". It has been written to depict the management of Coronavirus in Indonesia generally and the view of the purposes of Sharia on it. The researcher explored the evidence and information about it by reading and tracing the transcript and based on the analytical deduction approach in estimating the procedures for managing Coronavirus in Indonesia from the theory of the purposes of Sharia. It follows from this research that the administration was conducted according to the guidelines from the World Health Organization, except in some cases that tended to present economic and political importance, contrary to the theory of the purposes of Sharia, which puts self-preservation first in the order. Following this result, the administration must take precedence over others in all future decisions; because it is achieved to ward off major evils and bring future interests.